2003
DOI: 10.1515/jpem.2003.16.8.1131
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Tests in Preterm Infants Born to Preeclamptic Mothers with Placental Insufficiency

Abstract: Low levels of thyroid hormones and high level of TSH in cord blood in premature infants born to preeclamptic mothers with placental insufficiency suggest intrauterine hypothyroidism. Increase in TSH and thyroid hormone concentrations after birth reveal that the hypothalamic-pituitary-thyroid axis is intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…35 In this study, umbilical fT 4 levels in the neonates were lower than in the comparison group, a finding in concordance with literature. 13,14,17,22,26 This low umbilical fT 4 was not related to maternal fT 4 , therefore it is not likely to result from decreased maternal supply of fT 4 or impaired transfer. According to our data, these Because gestational age in the study group was 3 weeks older than in the comparison group, higher concentrations of TT 4 , fT 4 , TT 3 , and TBG were anticipated in the study group, explaining the higher TT 3 levels found.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…35 In this study, umbilical fT 4 levels in the neonates were lower than in the comparison group, a finding in concordance with literature. 13,14,17,22,26 This low umbilical fT 4 was not related to maternal fT 4 , therefore it is not likely to result from decreased maternal supply of fT 4 or impaired transfer. According to our data, these Because gestational age in the study group was 3 weeks older than in the comparison group, higher concentrations of TT 4 , fT 4 , TT 3 , and TBG were anticipated in the study group, explaining the higher TT 3 levels found.…”
Section: Discussionmentioning
confidence: 81%
“…18 -21 Free T 4 is generally found to be lower in umbilical cord samples from neonates born from preeclamptic pregnancies than in infants from normotensive pregnancies, but reports remain inconclusive. 13,14,17,[22][23][24][25][26] A low fT 4 can be a consequence of lower maternal thyroid hormone levels; however, it can also be caused by impaired transfer of T 4 due to placental insufficiency or fetal disease due to fetal growth restriction (FGR) and fetal acidosis.…”
mentioning
confidence: 99%
“…We also observed an association between higher neonatal TSH levels in infants born to mothers with preeclampsia. Two studies found higher cord blood TSH in preterm neonates born to mothers with preeclampsia; however, other studies, some of which evaluated term infants, have not observed this finding (7, 12, 27, 28). Our findings, in combination with the other studies that found higher neonatal TSH levels in preterm infants born to mothers with preeclampsia, suggest that there may be placental insufficiency and/or fetal hypoxia which in turn triggers higher TSH levels in the neonate.…”
Section: Discussionmentioning
confidence: 95%
“…Placental insufficiency (PI) occurs when functional capacity of the placenta is limited or deteriorates, resulting in reduced transplacental transfer of oxygen and nutrients to the fetus (Gagnon 2003). Reduction or impairment of placental blood flow (Chaddha et al 2004), aberrant fibrin depositions or other thrombo-occlusive damage in the placenta (Chaddha et al 2004), and disruption of maternal-placental THs (Belet et al 2003) are all believed to contribute to PI pathogenesis in women. We provide evidence illustrating pathological and physiological features that are concordant with PI in our experimental mouse model.…”
Section: Discussionmentioning
confidence: 99%